2017
DOI: 10.1038/s41467-017-01678-y
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected protein interaction promotes drug resistance in leukemia

Abstract: The overall survival of patients with acute myeloid leukemia (AML) is poor and identification of new disease-related therapeutic targets remains a major goal for this disease. Here we show that expression of MPP1, a PDZ-domain-containing protein, highly correlated with ABCC4 in AML, is associated with worse overall survival in AML. Murine hematopoietic progenitor cells overexpressing MPP1 acquired the ability to serially replate in methylcellulose culture, a property crucially dependent upon ABCC4. The highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…TR-FRET screen for identifying MAGE-A11 small molecule inhibitors was performed as follows. The primary one-concentration screening and subsequent 10 or 20-concentration dose-response tests were accomplished with an automated High Throughput Screening system (HighRes Biosolutions, Beverly, MA) 30 . In the primary screening, 15 µl/well FAM-PCF11_4 (267 nM) was first dispensed with a Multidrop Combi Reagent Dispenser (Thermo Fisher Scientific, Waltham, MA) to black 384-well low-volume assay plates.…”
Section: Methodsmentioning
confidence: 99%
“…TR-FRET screen for identifying MAGE-A11 small molecule inhibitors was performed as follows. The primary one-concentration screening and subsequent 10 or 20-concentration dose-response tests were accomplished with an automated High Throughput Screening system (HighRes Biosolutions, Beverly, MA) 30 . In the primary screening, 15 µl/well FAM-PCF11_4 (267 nM) was first dispensed with a Multidrop Combi Reagent Dispenser (Thermo Fisher Scientific, Waltham, MA) to black 384-well low-volume assay plates.…”
Section: Methodsmentioning
confidence: 99%
“…Examples include pitavastatin, which has an IC 50 value of 84 nM. The general screening process and data analysis have been previously described [1215].…”
Section: Methodsmentioning
confidence: 99%
“…It is also interesting that MPP1 is highly www.fhc.viamedica.pl abundant in AML (acute myeloid leukemia) cells, and interacts with the ABC transporter, ABCC4. The studies by Pitre et al [52] showed that the expression of MPP1 highly correlated with ABCC4 expression in AML, and moreover, it was also associated with poor prognosis for AML patients. The authors carried out an assessment of all PDZ-binding domain proteins on the oligonucleotide microarray with samples from the diagnostic leukemic blasts of 130 pediatric AML patients.…”
Section: Mpp1 Interacts With Different Proteinsmentioning
confidence: 99%
“…Furthermore, MPP1 regulates ABCC4 plasma membrane location and affects stability of ABCC4. Further research of this group indicated that this protein interaction is readily disrupted by a small molecule, antimycin A [52].…”
Section: Mpp1 Interacts With Different Proteinsmentioning
confidence: 99%